Roadmap for institutionalizing agricultural data hub in Mali - Diallo, Aboubacar; Bengaly, O; Dossou-Yovo, E.R (2025)
Agricultural Data Hub (Ag-Data Hub) in Mali is a transformative digital platform central to the country strategy for modernizing agriculture and enhancing climate resilience. It consolidates agro-climatic, agronomic, and market data to support decision-making by farmers, researchers, policymakers, and private sector actors. Recognized as a digital public good, the hub is anchored in national strategies and institutions such as Mali-Météo, and benefits from inclusive, multi-stakeholder governance and blended financing. To ensure sustainability, the hub is integrated into Mali national digital agriculture strategy, backed by a hybrid financing model, and strengthened through capacity building in collaboration with research and academic institutions. Efforts to expand usage include training-of-trainers (ToT) programs, integration into agricultural education, grassroots trainings, media outreach, and development of multilingual support tools. For last-mile delivery, Mali leverages mobile advisories, Farmer Field Schools, extension networks, rural radio, and farmer organizations to deliver localized, actionable insights. Feedback mechanisms like mobile surveys and participatory sessions enhance relevance and trust. Strong demand from government ministries, researchers, private sector, and underserved groups including women, youth, and non-rice sectors underscores the hub utility and the need for expanded features and coverage. Under AICCRA Phase 3, the focus will be on scaling capacity development, enriching content, bundling digital services, and formalizing a national agricultural data-sharing policy. These efforts aim to entrench the Ag-Data Hub as a key element of Mali digital agriculture landscape and as a replicable model for West Africa.